2020
DOI: 10.1002/bmb.21391
|View full text |Cite
|
Sign up to set email alerts
|

Students' use of chemistry core ideas to explain the structure and stability of DNA

Abstract: Students tend to think of their science courses as isolated and unrelated to each other, making it difficult for them to see connections across disciplines. In addition, many existing science assessments target rote memorization and algorithmic problem‐solving skills. Here, we describe the development, implementation, and evaluation of an activity aimed to help students integrate knowledge across introductory chemistry and biology courses. The activity design and evaluation of students' responses were guided b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…In our Ocean Acidification activity, 93% were able to correctly predict the relationship between CO 2 and pH, with 43% of students further making the correct prediction regarding how changes in the pH of the ocean could affect shelled organism. These results are similar to the implementation and evaluation of previously developed multidisciplinary activities, where we found that in general (1) students found the activities useful to connect ideas and disciplines they would not have otherwise, and (2) while many students could provide sophisticated responses that incorporated their understanding of chemistry ideas to explain the chemistry phenomena, they had difficulties using the same ideas to explain biological phenomena. Thus, previous , and current work highlights the importance of supporting students through the use of knowledge by providing them with experiences similar to the one presented in this study. Even, if students struggle to make the desired connections, we need to provide them with such opportunities to grow and learn.…”
Section: Summary Implications For Teaching and Limitationssupporting
confidence: 83%
See 2 more Smart Citations
“…In our Ocean Acidification activity, 93% were able to correctly predict the relationship between CO 2 and pH, with 43% of students further making the correct prediction regarding how changes in the pH of the ocean could affect shelled organism. These results are similar to the implementation and evaluation of previously developed multidisciplinary activities, where we found that in general (1) students found the activities useful to connect ideas and disciplines they would not have otherwise, and (2) while many students could provide sophisticated responses that incorporated their understanding of chemistry ideas to explain the chemistry phenomena, they had difficulties using the same ideas to explain biological phenomena. Thus, previous , and current work highlights the importance of supporting students through the use of knowledge by providing them with experiences similar to the one presented in this study. Even, if students struggle to make the desired connections, we need to provide them with such opportunities to grow and learn.…”
Section: Summary Implications For Teaching and Limitationssupporting
confidence: 83%
“…This Ocean Acidification activity is one of seven activities developed to support students with integrating and using chemistry core ideas to explain biological phenomena. Among the faculty members at our institution, ocean acidification was identified as a phenomenon of high value from a list of biology topics that require chemistry ideas to be explained due to the coastal location of the university of interest in the Southeastern United States. In addition, previous research has revealed the low awareness and understanding of ocean acidification among biology, chemistry, and biochemistry students in comparison to other science students .…”
Section: Activity Development and Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of interdisciplinary learning at the undergraduate level has increased in science education discourse. These efforts include large projects (for example, the BRAID project), as well as smaller, single-activity research articles, such as those proposed by Underwood et al While interdisciplinarity may focus on the integration of science with social and economic studies (for example, addressing climate change or sustainability issues), students should also be able to integrate ideas between their science courses, such as chemistry and biology, particularly prehealth students who need to leverage both disciplines in their future courses and careers. Students in undergraduate STEM majors frequently enroll in both chemistry and biology courses to meet their degree requirements.…”
Section: Background and Significancementioning
confidence: 99%
“…We are developing activities (Matz et al, 2019;Roche Allred et al, 2021) that provide opportunities for students to connect ideas across two disciplines at the undergraduate level: general chemistry and introductory cell and molecular biology. These disciplines are of interest for at least two reasons.…”
mentioning
confidence: 99%